MODEL PENGUATAN KARAKTER ISTIQOMAH PADA KELUARGA TAHFIDZUL QUR'AN (STUDI MULTISITUS DI 4 KECAMATAN SE-PASURUAN RAYA) - Seyla Dwi Noviska; Muhammad Muhlis (As-Sulthan Journal of Education, 2026)
This study examines the role of Tahfidzul Qur'an families in strengthening the character of istiqomah among children. It aims to identify the values of istiqomah character and analyze the family education model that supports its development. A qualitative approach with a multi-site design was employed involving five Tahfidzul Qur'an families in Pasuruan Raya. Data were collected through in-depth interviews, observation, and documentation, and analyzed using within-site and cross-site analysis. The findings reveal that istiqomah is reflected in consistency in muraja'ah, time discipline, responsibility, patience, self-awareness, and religious commitment. These values are strengthened through a family education model based on parental role modeling, habituation of worship and muraja'ah, continuous guidance, spiritual motivation, and a supportive Qur'anic environment. The study concludes that family-based Tahfidz education plays a crucial role in developing sustainable religious character and maintaining consistency in practicing Qur'anic values.